PENDIDIKAN SEKSUALITAS REMAJA DALAM KELUARGA DI DESA KATANA KECAMATAN TOBELO TIMUR KABUPATEN HALMAHERA UTARA - S. Pakey, Erik Yohanis S. (Universitas Sam Ratulangi, 2016)
Sexuality education to the children in the family in the Katana village of Kecamatan Tobelo Kabupaten Halmahera Utara different to other communities in indonesia. In terms of sexuality education, the parents never talked openly to their children. It is influenced by other traditional mindset that there are many negative things said in the sexuality so it is not meant to be topic against children. If there is stated or teenage sexuality means discuss already violating the customs of the norm and regarded violate ethics norm manners. A clash of reality where teenagers can get information about sexuality face with rigid attitude means community perspective about sexuality on his teenage son, most teenagers then seek and find answers each about sexuality. Due to, most teenagers misrepresented the meaning of sexuality. This research attempts to see how the parents of students teenager and how the promiscuity teenager in the Katana village. Using approach qualitative methodology, and engineering data collection by interviews, observation and literature review. The result of this research suggests that not all parents aware of understanding education sexuality the truth. So that the pattern students from parents teenagers are not going well. Hopefully can help understand the meaning of sex the truth, that should be the boy early be landing on sex education by their parents. That as a teenager and adult years he knew about her from their parents without paying they have curiosity and find the answer in intercourse. Keywords: children, sexuality education, teenagers